Analysis of the Efficacy and Safety of Endoscopic Retrograde Cholangiopancreatography in Children With Symptomatic Pancreas Divisum - Pan, Guixian; Yang, Kaihua; Gong, Biao; Deng, Zhaohui (Frontiers in Pediatrics, 2021)
Background Endoscopic retrograde cholangiopancreatography (ERCP) has been increasingly used in children with symptomatic pancreas divisum(PD). Aim To investigate the safety and efficacy of ERCP in the treatment of children with symptomatic PD. Methods We performed a retrospective analysis of children with PD who treated with ERCP at Shanghai Children’s Medical Center between June 2015 and May 2020 .Pertinent patient,clinical and procedure information was collected to assess the therapeutic effects and the risk factors for post-ERCP pancreatitis (PEP). Results Altogether, 114 ERCPs were performed in 46 children with PD. With a median follow-up of 28.5 months (12-71 months), forty (87.0%) children achieved clinical remission, the median number of acute pancreatitis episodes decreased from 4 times /year preoperatively to 1 times/year postoperatively (P = 0.000), and the nutritional score improved postoperatively (P = 0.004). Post-ERCP complications occurred in 12 (10.5%) patients (PEP, 9; infections, 3), and they improved with conservative management. The incidence of PEP was 7.9%, and female sex, stone extraction, and gene mutations were possible risk factors for PEP on univariate analysis. However, there was no statistical significance on multivariate analysis (P > 0.05). Conclusion Therapeutic ERCP is an effective and safe intervention for children with symptomatic PD.